Diffusion- and Perfusion-Weighted MR Imaging of Dural Sinus Thrombosis - Manzione, James (AJNR Am J Neuroradiol, 2000)
Summary: A patient with dural sinus thrombosis had progressively worsening symptoms and signs that resolved after intradural thrombolysis. Intradural sinus pressures were 54 mm Hg. Echo-planar MR imaging revealed complex abnormalities of diffusion and widespread delay in mean transit time that improved immediately after thrombolysis. This case suggests that diffusion- and perfusion-weighted imaging can provide valuable information noninvasively to help triage patients with dural sinus thrombosis between conservative and aggressive management.